2012
DOI: 10.1159/000338799
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transforming Growth Factor-β1 Activation and Expression in the Tissue Remodeling Involved in Chronic Rhinosinusitis

Abstract: Transforming growth factor-β1 (TGF-β1) plays a key role in the tissue remodeling processes involved in chronic rhinosinusitis (CRS), with the biological functions of secreted TGF-β1 regulated by multiple proteins. Among these regulators, latency-associated peptide and latent TGF-β-binding protein inhibit TGF-β1 function, whereas different proteases and integrins activate it. Progress in understanding the factors responsible for the bioactivity and expression of TGF-β1 has revealed that the dysregulation of TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 75 publications
(40 reference statements)
0
22
1
Order By: Relevance
“…Many previous papers in western countries have reported that patients with CRSsNP showed higher levels of TGF-β expression, whereas those with CRSwNP showed lower TGF-β expression levels compared with the control subjects [6, 14, 16, 17]. However, there was no significant difference in TGF-β between our ECRS and non-ECRS groups.…”
Section: Discussioncontrasting
confidence: 55%
“…Many previous papers in western countries have reported that patients with CRSsNP showed higher levels of TGF-β expression, whereas those with CRSwNP showed lower TGF-β expression levels compared with the control subjects [6, 14, 16, 17]. However, there was no significant difference in TGF-β between our ECRS and non-ECRS groups.…”
Section: Discussioncontrasting
confidence: 55%
“…Typically, it has been divided into CRSwNP and CRSsNP based on the presence or absence of polyps on endoscopic examinations [1]. CRS results in a substantial burden with a prevalence of about 12.5% in the population [50] and is estimated to affect over 10 million patients in the US, leading to total annual costs of USD 22 billion [51]. Besides inflammation, these chronic upper airway disorders are characterized by remodeling of structural components, especially of the epithelium [13].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Moreover, the TGF-β1 signaling pathway has been reported to have close contact with the AhR signaling pathway, and a crosstalk might exist between AhR and TGF-β1. Recently published data revealed that AhR, which is a unique intracellular protein, might play a key role in modulating the mucosal structural integrity by regulating TGF-β1 expression [1,25]. The AhR-/- fibroblasts secreted obviously more TGF-β1 than the AhR+/+ fibroblasts, and the AhR-/- fibroblasts indicated increased activated TGF-β1 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic rhinosinusitis (CRS) is a chronic inflammatory disease involving the nasal cavity and sinus mucosa, which results in a substantial burden with a prevalence of about 12.5% of the population [1]. CRS includes two types: CRS with nasal polyps (CRSwNP) and CRS without nasal polyps (CRSsNP) [2].…”
Section: Introductionmentioning
confidence: 99%